Between Scepticism and Adoption: A Phenomenological Study of Indonesian EFL Teachers' Lived Experiences Integrating Generative AI into Writing Instruction - Muhammad Nasheh Ulwan (Journal of Innovation in English Education and Language Teaching, 2026)
While survey research has mapped the contours of EFL teacher attitudes towards generative AI, the lived, day-to-day experience of teachers who are actively attempting to integrate these tools into writing instruction remains underexplored. This study uses interpretive phenomenological analysis (IPA) to examine how nine Indonesian EFL lecturers experienced the process of integrating generative AI tools into their academic writing courses over one academic semester. Data were collected through three rounds of in-depth interviews and reflective teaching journals kept throughout the integration period. Findings reveal a phenomenological landscape characterised by productive tension: teachers navigated ongoing oscillation between intellectual curiosity and pedagogical anxiety, between the sense of professional obligation to engage with new tools and the felt inadequacy of their preparation to do so responsibly, and between their desire to help students use AI well and their uncertainty about what using AI well actually looks like in a writing classroom. Four experiential themes organise the findings: the vertigo of not knowing enough, the loneliness of navigating without a map, the satisfaction of unexpected pedagogical discovery, and the moral weight of institutional silence. The study draws on Merleau-Ponty's (1962) phenomenology of embodied experience and van Manen's (2016) hermeneutic phenomenology to argue that teacher AI integration is not primarily a knowledge problem or a skills problem but an experiential one and that addressing it requires professional support structures that attend to the phenomenological dimensions of teachers' encounters with AI in their specific professional contexts.